A comprehensive review of Pt electrocatalysts for the oxygen reduction reaction: nanostructure, activity, mechanism and carbon support in PEM fuel cells - Sui, Sheng; Wang, Xiaoying; Zhou, Xintong; Su, Yuehong; Riffat, Saffa; Liu, Chang-jun (Royal Society of Chemistry, 2017)
The sluggish rate of the oxygen reduction reaction (ORR) in proton exchange membrane (PEM) fuel cells has been a major challenge. Significantly increasing efforts have been made worldwide towards a highly active ORR catalyst with high durability. Among all the catalysts exploited, Pt electrocatalysts are still the best in terms of a comprehensive evaluation. The investigation of Pt-based ORR catalysts is necessary for a practical ORR catalyst with low Pt content. This paper reviews recent progress in the studies of the mechanism, nanostructure, size effect and carbon supports of Pt electrocatalysts for the ORR. The importance of the size and structure control of Pt ORR catalysts, related with carbon support materials, is indicated. The potential methods for such control are discussed. The progress in theoretical studies and in situ catalyst characterization are also discussed. Finally, challenges and future developments are addressed.